Functional dependence and caregiver burden in Alzheimer's disease: a controlled trial on the benefits of motor intervention - Canonici, Ana Paula; de Andrade, Larissa Pires [UNESP]; Gobbi, Sebastiao [UNESP]; Santos-Galduroz, Ruth Ferreira; Bucken Gobbi, Lilian Teresa [UNESP]; Stella, Florindo [UNESP] (Wiley-Blackwell, 2012)
Background: Cognitive decline has a negative impact on functional activities in Alzheimer's disease. Investigating the effects of motor intervention with the intent to reduce the decline in functionality is an expected target for patients and caregivers. The aim of this study was to verify if a 6-month motor intervention programme promoted functionality in Alzheimer's patients and attenuated caregivers' burden. Methods: The sample comprised 32 community patients with Alzheimer's disease and their 32 respective caregivers. Patients were divided into two groups: 16 participated in the motor intervention programme and 16 controls. Subjects performed 60 minutes of exercises, three times per week during the 6-month period, to improve flexibility, strength, agility and balance. Caregivers followed the procedures with their patients during this period. Functionality was evaluated by the Berg Functional Balance Scale and the Functional Independence Measure. Caregivers completed the Neuropsychiatric Inventory Caregiver Distress Scale and the Zarit Carer Burden Scale. Two-way ANOVA was used to verify the interaction between time (pre- and post-intervention) and the motor intervention program. Results: While patients in the motor programme preserved their functionality, as assessed by the Functional Independence Measure, the controls suffered a relative decline (motor intervention group: from 109.6 to 108.4 vs controls: from 99.5 to 71.6; P= 0.01). Patients from motor intervention also had better scores than the controls on functional balance assessed by Berg scale (F: 22.2; P= 0.001). As assessed by the Neuropsychiatric Inventory and Zarit scale, burden was reduced among caregivers whose patients participated in the motor intervention programme compared with caregivers whose patients did not participate in this programme (Neuropsychiatric Inventory, caregiver's part: F: 9.37; P= 0.01; Zarit: F: 11.28; P= 0.01). Conclusion: Patients from the motor intervention group showed reduced functional decline compared to the controls, and there was an associated decrease in caregivers' burden.
Keywords: Alzheimer's disease; caregiver burden; functionality; motor intervention